Human and State Security: Case Studies of Indonesian Community in Dealing with The Covid-19 Pandemic - Riyanta, Stanislaus; Handayani, Riska Sri (International Journal of Strategic Studies, 2024)
During the Covid-19 pandemic, nearly every country was vulnerable to the impact of the outbreak. Even countries renowned for their advanced healthcare systems found themselves helpless. Indonesia, with a population exceeding 270 million, was not exempted, as 6,811,330 confirmed cases, 6,640,002 recoveries, and 161,848 deaths were reported in June 2023. The pandemic also had detrimental effects on the already struggling economy, as various restrictions hindered both economic growth and mobility. However, compared to other nations, Indonesia showcased greater resilience. According to the Ministry of Health, the country experienced the most controlled increase in Covid-19 cases compared to five other Asian countries, namely India, the Philippines, Singapore, Malaysia, and Thailand. The data from the Fiscal Policy of the Indonesian Ministry of Finance showed Indonesia's economy managed to grow by 3.69% in 2021, surpassing the average economic growth rate of other ASEAN countries, which stood at 2.9% in the same year. The two indicators in the health and economic fields showed that the Indonesian community could endure and adapt to disaster situations. The emergence of community-driven initiatives during the pandemic, such as mutual assistance and support for those affected by Covid-19, further underscored the strength of the community. Moreover, the varied circumstances experienced revealed a relatively high level of human security, a factor that directly influenced national resilience in the face of the pandemic. The United Nations Development Programme (UNDP) identified seven components of human security, namely security, economy, food, health, environment, individual, community, and political aspects. Human security aimed to safeguard individuals against various threats to their well-being and was a crucial aspect of state protection in providing a sense of security to citizens. This study delved into the discussion of human security in Indonesia as a protective mechanism that encompassed both personal and communal security, and its direct influence on national resilience, particularly during the Covid-19 pandemic. The handling of the pandemic revealed the considerable strength of human security within the Indonesian community, facilitating the transition from a pandemic phase to an endemic phase of Covid-19 while upholding national resilience. Therefore, exploring the potential of human security was imperative, as it aimed to support national resilience beyond the scope of state security alone. This qualitative study concluded that a strong level of human security generally contributed to enhancing national resilience. Therefore, government approaches to implementing human security were expected to address the cultural backgrounds and customs of local communities. Human security was also considered a significant aspect and serious concern for the state, particularly in safeguarding national resilience during severe threats to the country.